Epistemology and metaphysics for qualitative research - Pernecky, Tomas (Los Angeles Sage Publications, 2016)
This clearly written and provocative text outlines the wide range of epistemological and metaphysical pillars of research. In a clear, easy to follow style, the reader is guided through an array of concepts that are defined, explained and made simple. With the aid of helpful examples and case studies, the book challenges the prevailing modes of thinking about qualitative inquiry by showcasing an immense variety of philosophical frameworks. Armed with a strong understanding of this philosophical backbone, students will be able to choose and defend a 'pick and mix' of research methods that will uniquely complement their research. Empiricism, Rationalismk, Realism, Skepticism, Idealism, Positivism, Post-positivism, Idea-ism, Hermeneutics, Phenomenology, Social Ontology, Quantum Mechanics Essential reading for new and experienced researchers, this 'must' for any social science bookshelf will help unlock a new level of research creativity.
Part I: Qualitative inquiry and philosophy -- Introduction: situating metaphysics and epistemology in qualitative research -- Part II: Key epistemological and metaphysical problems -- In search of truths: epiricism versus rationalism -- Scepticism, idea-ism, and idealism -- German idealism, phenomenology, and hermeneutics -- Realism, its varieties and contenders -- Part III: Intangible realities -- Social ontology -- Quantum reality: contemporary views of the things-in-themselves -- Part IV: Philosophy in qualitative research -- Conclusions: On academic creativity and philosophical and methodological freedom.
Includes bibliographical references (pages 209-229) and index.
Keywords: Qualitative research; Knowledge, Theory of; Metaphysics